Teucrium moleromesae (Lamiaceae): a new species of genus Teucrium sect. Montanum from the arid mountains of south-eastern Spain - Sánchez-Gómez, Pedro; Navarro, Teresa; Jiménez, Juan F.; Vera, Juan B.; Mota, Juan F.; Del Río, Jesus (Phytotaxa, 2013)
Teucrium moleromesae, a new species belonging to the section Montanum, is described and illustrated. The new species is compared with two taxonomically related species, T. terciae and T. pumilum. T. moleromesae occurs in open arid mountain in the north of Almeria and Granada provinces (south-eastern Spain). In addition, a distribution map, iconography, and a description of the habitat and conservation status of the new species are presented.